2018
DOI: 10.1007/s00701-018-3683-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological management of post-traumatic seizures in adults: current practice patterns in the UK and the Republic of Ireland

Abstract: Background Patient selection for seizure prophylaxis after traumatic brain injury (TBI) and duration of anti-epileptic drug treatment for patients with early post-traumatic seizures (PTS), remain plagued with uncertainty. In early 2017, a collaborative group of neurosurgeons, neurologists, neurointensive care and rehabilitation medicine physicians was formed in the UK with the aim of assessing variability in current practice and gauging the degree of uncertainty to inform the design of future stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 11 publications
0
14
1
Order By: Relevance
“…We recognise that our study was conducted on patients with a GCS 14-15, where dizziness could accurately be assessed, whereas the guidelines for AEDs in TBI are for those patients with severe TBI and GCS < 8. It is clear that AEDs are often prescribed for minor TBI based on clinician choice and it is this cohort that contributed [21]. Whether the AED was indicated at all in these patients was beyond the scope of this study.…”
Section: Percetage Of Patientsmentioning
confidence: 99%
“…We recognise that our study was conducted on patients with a GCS 14-15, where dizziness could accurately be assessed, whereas the guidelines for AEDs in TBI are for those patients with severe TBI and GCS < 8. It is clear that AEDs are often prescribed for minor TBI based on clinician choice and it is this cohort that contributed [21]. Whether the AED was indicated at all in these patients was beyond the scope of this study.…”
Section: Percetage Of Patientsmentioning
confidence: 99%
“…A recent survey of neurosurgical centres in the UK suggests that 50% of neurosurgical centres routinely use anticonvulsants for seizure prophylaxis after brain injury. 50 Current evidence indicates that levetiracetam has a better safety profile and equal efficacy to phenytoin. Levetiracetam may also be associated with better functional outcomes.…”
Section: Seizures Prophylaxismentioning
confidence: 99%
“…Taken together, the proportion of patients receiving the recommended seizure prophylaxis in this study is lower than that found by others. In survey studies, self-reported use of the recommended seven-day seizure prophylaxis ranges from 38 to 50% [14,23]. Even though 26-65% of TBI patients were found to have been started on seizure prophylaxis in studies that employed medical record reviews, the duration of anticonvulsant use was not reported in two of these three studies [24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…A large, multicentre European study found significant variability in indications for and duration of seizure prophylaxis and identified that although nearly all centres reported the use of practice guidelines for the management of TBI, fewer than half had policies that included seizure prophylaxis [21,22]. Surveys in the United Kingdom and Ireland have found that seizure prophylaxis is prescribed by fewer than 60% of responding neurosurgeons, among whom only 38-50% prescribe anticonvulsants for the recommended seven days [14,23]. North American retrospective medical record reviews have found seizure prophylaxis rates of 26-65% [24][25][26].…”
Section: Introductionmentioning
confidence: 99%